2020
DOI: 10.1021/acs.est.9b07785
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Changes in Summertime Surface Ozone–NOx–VOC Chemistry over U.S. Urban Areas from Two Decades of Satellite and Ground-Based Observations

Abstract: Urban ozone (O3) formation can be limited by NO x , VOCs, or both, complicating the design of effective O3 abatement plans. A satellite-retrieved ratio of formaldehyde to NO2 (HCHO/NO2), developed from theory and modeling, has previously been used to indicate O3 formation chemistry. Here, we connect this space-based indicator to spatiotemporal variations in O3 recorded by on-the-ground monitors over major U.S. cities. High-O3 events vary nonlinearly with OMI HCHO and NO2, and the transition from VOC-limited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
179
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 186 publications
(240 citation statements)
references
References 82 publications
(182 reference statements)
15
179
1
1
Order By: Relevance
“…The hourly comparison of mean concentration values of March and April 2019 with March and April 2020 showed a declining trend in O 3 concentrations. This diurnal variation in this station suggested that O 3 concentrations have been reduced during the lockdown period in response to a decrease in ozone precursor emissions, as NO x , occurring in rural areas (Jin et al 2020;Simon et al 2015). Meteorological conditions, such as temperature, could affect the O 3 trends but, as discussed previously, the meteorological data were almost similar prior to and during the lockdown periods, not influencing changes in air pollutant concentrations.…”
Section: Background Stationssupporting
confidence: 56%
See 1 more Smart Citation
“…The hourly comparison of mean concentration values of March and April 2019 with March and April 2020 showed a declining trend in O 3 concentrations. This diurnal variation in this station suggested that O 3 concentrations have been reduced during the lockdown period in response to a decrease in ozone precursor emissions, as NO x , occurring in rural areas (Jin et al 2020;Simon et al 2015). Meteorological conditions, such as temperature, could affect the O 3 trends but, as discussed previously, the meteorological data were almost similar prior to and during the lockdown periods, not influencing changes in air pollutant concentrations.…”
Section: Background Stationssupporting
confidence: 56%
“…Accordingly, there are two sensitivity regimes of O 3 production, namely, the NO x -limited and VOC-limited regimes. In the NO x -limited regime, generally in rural areas (Jin et al 2020), an increase in NO x values leads to an increase in ozone production which shows to be only slightly affected by VOC variations. In the VOC-limited regime, generally in urban areas (Witte et al 2011), ozone increases with increasing VOC and decreases with increasing NO x .…”
Section: Introductionmentioning
confidence: 98%
“…For example, NO x emissions can titrate (i.e., remove) ozone, reducing concentrations. Therefore, lower NO 2 can, in some cases and depending on the chemistry [47][48][49][50][51] , lead to higher ozone levels; this potential pattern may be especially important in urban areas. Decreasing NO 2 increases VOC:NOx ratios, which can increase secondary organic aerosol yields, leading to increased PM 2.5 concentrations [52][53][54][55][56] .…”
Section: Discussionmentioning
confidence: 99%
“…The satellite-based HCHO to NO 2 ratio has been used to infer whether ozone formation is limited by NO x or VOCs or in transition between regimes (Duncan et al, 2010;Jin & Holloway, 2015;Martin et al, 2004). Our ongoing research demonstrates that satellite-based HCHO/NO 2 generally captures the observed nonlinear dependence of ozone production on NO x and VOCs (Jin et al, 2020). In addition, observed decadal changes in spatiotemporal patterns of ground-level ozone, known to occur as ozone formation chemistry transitions to stronger NO x sensitivity, are linked directly to satellite HCHO/NO 2 trends over several U.S. metropolitan areas.…”
Section: 1029/2020gh000270mentioning
confidence: 97%